Esteem report / Muhamad Haziq Hamidon ... [et al.] - Hamidon, Muhamad Haziq; Muhammad Rus, Muhammad Fazli; Mazlan, Mohamad Husyafiq Asraf; Harith-Rathi, Muhammad Haziq (Faculty Of Civil Engineering, 2018)
Column foundation design, pad footing detailed design calculation.